Christianity in Modern Bourgeois Society - Gendrolis, Edmundas (Problemos, 1973)
In modern bourgeois society Christianity has lost to a considerable extent its transcendentalism, and its social doctrine comes to the fore. In the race of social antagonism in that society, the ideological struggle or the two social systems in the world, the wide dissemination of socialist and communist ideas, religious organizations concentrate their activities more and more on social problems. Being considered as one of social and cultural values in bourgeois society, religion acquires political significance in the ideological struggle ant it is used, therefore, as an ideological weapon in the fight against communist ideology.